PENGARUH MANAJEMEN LABA DAN FINANCIAL DISTRESS TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Henni Rahayu Handayani; Siti Mardiansyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Various methods are used to maintain profits, including minimizing the tax burden. For companies, tax is an expense that has a significant effect on reduced profits. So, taking concrete steps to reduce tax payments is a must. In fact, this study tries to analyze the factors that are usually carried out by companies in minimizing tax payments. For this reason, quantitative methods are used with multiple linear regression analysis. The companies used as research samples are manufactures listed on the Indonesian stock exchange, with a total of 56 data. The results confirm that the action to reduce tax payments made by the company is generally classified as planned. However, the actions taken were taking into account the applicable tax regulations, namely by taking advantage of an unstable financial situation and controlling operating profit. In other words, it is possible to reduce tax costs in the manufacturing sector, because there are many gaps in business operations.